Chilean underground mine dataset. (January 2017) - Leung, Keith; Lühr, Daniel; Houshiar, Hamidreza; Inostroza, Felipe; Borrmann, Dorit; Adams, Martin; Nüchter, Andreas; Ruiz del Solar, Javier
This article presents a robotic dataset collected from the largest underground copper mine in the world. The sensor measurements from a 3D scanning lidar, a 2D radar, and stereo cameras were recorded from an approximately two kilometer traverse of a production-active tunnel. The equipment used and the data collection process is discussed in detail, along with the format of the data. This dataset is suitable for research in robotic navigation, as well as simultaneous localization and mapping. The download instructions are available at the following websitehttp://dataset.amtc.cl .